Kepemimpinan Partisipatif Dalam Meningkatkan Mutu Sekolah - Hansein Arif Wijaya (Departement of Mathematics Education, 2023)
This research aims to describe the implementation of participative leadership style by the school principal in a high school. The research method employed is qualitative descriptive. The research subjects consist of the school principal and the teachers. Data collection techniques include interviews, observation, and documentation methods. Data analysis techniques were carried out concurrently, including data reduction, presentation, and drawing conclusions. The research results indicate that the school principal utilizes leadership in accordance with the characteristics of their subordinates to enhance the school's quality. In their leadership, the school principal encourages subordinates to develop creativity, provides opportunities for subordinates to make decisions, prioritizes consensus for common interests, and fosters leadership regeneration and cadre expansion. It is expected that this will enable the school principal to continue fostering good relationships with subordinates to enhance the school's quality.